2011
DOI: 10.1213/ane.0b013e31820a5626
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Classic and a Modified Laryngeal Mask Airway (OPLAC™) in Adult Patients

Abstract: Both devices have comparable airflow resistance and are easy to insert. The OPLAC requires less insertion time, has less variation on insertion time, fits better into the laryngopharynx, is less likely to cause gastric insufflations, and has a higher sealing pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Our findings with respect to the first attempt success rate of LMA-C insertion and adequate ventilation in the young group (96%) compares well with the results of previous studies [ 15 23 ]. Previous studies demonstrated that the first attempt success rate in adults (mean age: 39.7-45.1 years) was 96.7-98.0% [ 15 23 ]. In our study, the number of elderly patients who needed further adjustment of the LMA-C position after initial insertion was greater than that of young patients.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our findings with respect to the first attempt success rate of LMA-C insertion and adequate ventilation in the young group (96%) compares well with the results of previous studies [ 15 23 ]. Previous studies demonstrated that the first attempt success rate in adults (mean age: 39.7-45.1 years) was 96.7-98.0% [ 15 23 ]. In our study, the number of elderly patients who needed further adjustment of the LMA-C position after initial insertion was greater than that of young patients.…”
Section: Discussionsupporting
confidence: 90%
“…A standard pre-use test was performed. Then, the cuff of the LMA-C was partially inflated with half the amount of air recommended by the manufacturer (size 3, 10 ml of air; size 4, 15 ml of air; and size 5, 20 ml of air) [ 13 14 15 ]. All devices were lubricated with a water-soluble gel.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Not surprisingly, as an established SGA with a proven clinical track record, the LMA has been and continues to be a standard for comparison. [4][5][6][7][8][9][10] The recently developed self-pressurized air-QÒ intubating laryngeal airway (air-Q SP) (Mercury Medical, Clearwater, FL, USA) is a single-use SGA that does not require cuff inflation. The original air-QÒ intubating laryngeal airway (Cookgas LLC; Mercury Medical) was designed to facilitate tracheal intubation through its lumen.…”
Section: Résumémentioning
confidence: 99%